Effects of Cyperin 10 EC and Neem extract on pollinator abundance, fruit setting and quality of mango (Journal of the Bangladesh Agricultural University, 2014)
Effects of cyperin 10 EC and neem extract on pollinators, fruit setting and fruit quality of mango was investigated. Number of pollinators visited mango inflorescences was higher in morning in comparison to noon and afternoon. In control plants, average 25.67 pollinators visited within 30 minutes which was higher than cyperin 10 EC (20.00) and neem extract treated (24.34) plants. The pollinators were under the order Hymenoptera (26.31%), Diptera (52.42%), Odonata (5.26%) and unidentified (10.53%). Bloomed and fertilized flowers were lower in cyperin treated plants than neem treated and control plants. Highest average fruit weight was obtained from neem treated plants, whereas cyperin treated plants gave lowest percentage of infested fruit and control plants gave highest percentage of deformed fruit. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19861 J. Bangladesh Agril. Univ. 11(2): 189-192, 2013